A Systematic Review and Meta-Analysis on the Safety of Vascular Endothelial Growth Factor (VEGF) Inhibitors for the Treatment of Retinopathy of Prematurity. - Laura Pertl; Gernot Steinwender; Christoph Mayer; Silke Hausberger; Eva-Maria Pöschl; Werner Wackernagel; Andreas Wedrich; Yosuf El-Shabrawi; Anton Haas (PLoS ONE, 2015)
Introduction Laser photocoagulation is the current gold standard treatment for proliferative retinopathy of prematurity (ROP). However, it permanently reduces the visual field and might induce myopia. Vascular endothelial growth factor (VEGF) inhibitors for the treatment of ROP may enable continuing vascularization of the retina, potentially allowing the preservation of the visual field. However, for their use in infants concern remains. This meta-analysis explores the safety of VEGF inhibitors. Methods The Ovid Interface was used to perform a systematic review of the literature in the databases PubMed, EMBASE and the Cochrane Library. Results This meta-analysis included 24 original reports (including 1.457 eyes) on VEGF inhibitor treatment for ROP. The trials were solely observational except for one randomized and two case-control studies. We estimated a 6-month risk of retreatment per eye of 2.8%, and a 6-month risk of ocular complication without the need of retreatment of 1.6% per eye. Systemic complications were only reported as isolated incidents. Discussion VEGF inhibitors seem to be associated with low recurrence rates and ocular complication rates. They may have the benefit of potentially allowing the preservation of visual field and lower rates of myopia. Due to the lack of data, the risk of systemic side effects cannot be assessed.